Evaluation of the Impact of the Youth Service: Youth Payment and Young Parent Payment - Keith McLeod; Sylvia Dixon; Sarah Crichton (New Zealand Government, The Treasury, 2016)
The Youth Service is a programme administered by the Ministry of Social Development, designed to encourage and assist disadvantaged youth to stay in education and achieve qualifications. There are three main strands of the programme. The Youth Service (YS) is provided to recipients of the Youth Payment (YP) and Young Parent Payment (YPP) benefits, while the YS:NEET service is aimed at disadvantaged young people at risk of becoming detached from employment, education and training. This report focusses on the YP and YPP strands. Community organisations are contracted to provide mentoring and support for youth participating in the service. This is complemented by other changes to youth benefits intended to encourage continued study, including; obligations to participate in the service and in formal study, financial incentives, sanctions for failing to meet obligations, and access to childcare payments.
Keywords: I38; J65; 330; Youth transitions; youth mentoring; social welfare programmes; unemployment; employment programmes; Jugendarbeitslosigkeit; Weiterbildung; Arbeitsvermittlung; Arbeitsmarktintegration; Beschäftigungseffekt; Junge Arbeitskräfte; Neuseeland